(NdIFFERENCIALXNYE SOOTNO[ENIQ S ^ASTNYMI PROIZWODNYMI (B/s - (NgROMOW(B, (NmIHAILs; (NmI[A^EW(B, (Nn(B.(Nm(B.s ((NmOSKWA (B:s (NmIR(B,s, 1990)
(NuKAZ(B. (NIMEN(B. (NI PREDM(B.: (NS(B. 524-534s
(NsPISOK LIT(B. (NS(B. 513-523s
Mikhael Gromov -
Keywords: (NdIFFERENCIALXNOE IS^ISLENIE(B. s